التشبيه عند أبي ذر مصعب بن مسعود الخشني "ت. 604" في كتابه الإملاء المختصر في شرح غريب السير - محمد، نهى جاسم; الجبوري، عبدالوهاب حسين خلف (جامعة تكريت - كلية التربية للعلوم الإنسانية, 2024)
تناولت في بحثي التشبيه وهو من أقسام علم البيان الأساسية، ويقوم البحث على استخرج الأغراض البلاغية للتشبيه وبيان أنواعها في كتاب الإملاء المختصر في شرح غريب السير، ومما يدل على أهميته لكثرة وروده في القرآن الكريم، والأحاديث النبوية الشريفة، وكلام العرب، والشعر العربي من خلال استعمال الصورة الشعرية التي استعان بها الشعراء لإبراز أفكارهم ومعانيهم وحياتهم في طرق مختلفة إذ وقف الخشني عند مسائل كثيرة من التشبيه وقفة متأنية ودقيقة من خلال شرحه للغريب الذي ورد ذكره في السيرة النبوية لابن هشام. This research deals with simile, which is one of the basic sections of the science of rhetoric. It is based on extracting the rhetorical purposes of simile and explain their types in the book Brief Dictation in Explanation of Gharib Al-Sir, and what indicates its importance due to its frequent occurrence in the Holy Qur’an and the noble hadiths of the Prophet, the words of the Arabs, and Arabic poetry through the use of poetic images that poets used to highlight their ideas, meanings, and lives in different methods, as Al- Khushani took a careful and precise stance on many issues of simile through his explanation of the stranger who was mentioned in the biography of the Prophet by Ibn Hisham.
Keywords: الأساليب البلاغية -- أنواع التشبيه -- الخشني، مصعب بن مسعود، ت. 604 هـ. -- كتاب الإملاء المختصر